Depot-specific adipocyte-extracellular matrix metabolic crosstalk in murine obesity. (1st January 2020) - Strieder-Barboza, Clarissa; Baker, Nicki A.; Flesher, Carmen G.; Karmakar, Monita; Patel, Ayush; Lumeng, Carey N.; O'Rourke, Robert W.
ABSTRACT: Subcutaneous (SAT) and visceral (VAT) adipose tissues have distinct metabolic phenotypes. We hypothesized that the extracellular matrix (ECM) regulates depot-specific differences in adipocyte metabolic function in murine obesity. VAT and SAT preadipocytes from lean or obese mice were subject to adipogenic differentiation in standard 2D culture on plastic tissue culture plates or in 3D culture in ECM, followed by metabolic profiling. Adipocytes from VAT relative to SAT manifested impaired insulin-stimulated glucose uptake and decreased adipogenic capacity. In 3D-ECM-adipocyte culture, ECM regulated adipocyte metabolism in a depot-specific manner, with SAT ECM rescuing defects in glucose uptake and adipogenic gene expression in VAT adipocytes, while VAT ECM impaired adipogenic gene expression in SAT adipocytes. These findings demonstrate that ECM-adipocyte crosstalk regulates depot-specific differences in adipocyte metabolic dysfunction in murine obesity.